2002
DOI: 10.1080/003655202320378176
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Short-Chain Fatty Acids on Iron Absorption by Proximal Colon

Abstract: The proximal colon could be a significant site available for iron absorption; this absorption can be enhanced by local production of short-chain fatty acids such as propionate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 24 publications
0
55
0
Order By: Relevance
“…Furthermore, animal studies have shown that the short chain fatty acids, in particular propionate seem to increase the absorption of iron in the colon proximal 2 . This may indicate a potential mechanism whereby ingestion of prebiotics increases the bioavailability of dietary iron.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, animal studies have shown that the short chain fatty acids, in particular propionate seem to increase the absorption of iron in the colon proximal 2 . This may indicate a potential mechanism whereby ingestion of prebiotics increases the bioavailability of dietary iron.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, iron absorption through the large intestine may contribute to the recovery from anemia in iron deficient rats 8,9 . It has indeed been shown that the lower digestive tract, especially the proximal colon, can also be an important site of iron absorption when the absorption in the small intestine is insufficient 2,3,8 as may be the case after gastrectomy 7 . Furthermore, rat studies have shown that short-chain fatty acids, and in particular propionate, appears to play a role in the increased absorption of iron in the proximal colon 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, animal studies have shown that the short chain fatty acids, in particular propionate seem to increase the absorption of iron in the colon proximal. This may indicate a potential mechanism whereby ingestion of prebiotics increases the bioavailability of dietary iron 31 .…”
Section: Fecal Iron and Apparent Iron Absorptionmentioning
confidence: 95%
“…However, the sufficient iron has been reported to be absorbed in the large intestine for recovery from anemia in iron deficient rats 29,30 . It has been showed that the proximal colon, can be an important site of iron absorption when the absorption in the small intestine is insufficient 25,29,31 , such as after the gastrectomy 32 . Furthermore, animal studies have shown that the short chain fatty acids, in particular propionate seem to increase the absorption of iron in the colon proximal.…”
Section: Fecal Iron and Apparent Iron Absorptionmentioning
confidence: 99%